2019
DOI: 10.1371/journal.pone.0216113
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine administration enhanced functional recovery after cuprizone demyelination

Abstract: The atypical antipsychotic agent, clozapine, is used to treat a variety of neurological disorders including schizophrenia and Parkinson’s disease and readily crosses the blood brain barrier to interact with a wide range of neuroreceptors including those for dopamine and serotonin. Recent work has shown that clozapine can reduce neuroinflammation in experimental autoimmune encephalomyelitis, a neuroinflammatory model of multiple sclerosis (MS) and mediates its effects in the central nervous system. To further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…Here, we used 0.3% cuprizone supplement in our animal facility since our previous pilot experiments reported insufficient demyelination or weight loss/behavioral deficits using 0.2%. Of note, compared to previous studies [47,50], we found a faster recovery after the withdrawal of cuprizone for 1 week, indicating a potential batch discrepancy when inducing the cuprizone model.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Here, we used 0.3% cuprizone supplement in our animal facility since our previous pilot experiments reported insufficient demyelination or weight loss/behavioral deficits using 0.2%. Of note, compared to previous studies [47,50], we found a faster recovery after the withdrawal of cuprizone for 1 week, indicating a potential batch discrepancy when inducing the cuprizone model.…”
Section: Discussioncontrasting
confidence: 79%
“…However, by performing behavioral test such as beam-walking test, pole test, and rotarod test, it was demonstrated by others and our group that cuprizone-treated mice show affected locomotor-coordinative function [ 15 , 25 , 27 , 45 , 46 ]. In general, most studies [ 24 , 47 , 48 ] used 6- to 9-week-old mice maintaining a diet containing 0.2–0.3% cuprizone for 5-6 weeks to induce CNS demyelination. The outcome effect of cuprizone-induced intoxication could vary depending on many factors, such as mouse strain, age, gender, and even the local environment in the animal facility [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5,6,[8][9][10] Previous work evaluating the effect of clozapine and risperidone treatment in two mouse models of multiple sclerosis (MS) has demonstrated a dose-dependent reduction in the severity of disease and improvement in disease resolution. [11][12][13] This protection correlates with reduced CNS inflammation, enhanced functional recovery, and can be achieved at doses that do not promote weight gain, a dosedependent side effect of both clozapine and risperidone. [12,13] Together this preclinical work suggests that clozapine and risperidone, which readily pass through an intact blood brain barrier and reduce neuroinflammation in mice and humans, [1] may be useful to treat the chronic neuroinflammation associated with progressive MS (pMS).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] This protection correlates with reduced CNS inflammation, enhanced functional recovery, and can be achieved at doses that do not promote weight gain, a dosedependent side effect of both clozapine and risperidone. [12,13] Together this preclinical work suggests that clozapine and risperidone, which readily pass through an intact blood brain barrier and reduce neuroinflammation in mice and humans, [1] may be useful to treat the chronic neuroinflammation associated with progressive MS (pMS). [14][15][16] To this end, the Clozapine and RISperidone in Progressive MS (CRISP) trial was designed to investigate to suitability of clozapine and risperidone treatment during pMS.…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine, an atypical antipsychotic drug, exerts antagonistic effects on multiple neurotransmitter receptors, such as serotonin 5-HT2, muscarinic M1, and dopamine D1, D2, and D4 receptors, and attenuates behavioral impairments in animal models of schizophrenia, including the neonatal polyI:C treatment model [60]. This antipsychotic drug has been reported to exhibit anti-in ammatory activities, and decrease astrocyte and microglial activation [61,62]. Thus, clozapine protects neurons from the in ammatory changes induced by poly I:C and prevents increases in interleukin-6 levels in the rodent brain [63,64].…”
Section: Discussionmentioning
confidence: 99%